Android-based Disease Monitoring - Woon, Chee Kok; Jane, Labadin; Aisyah, Mohammad; Kok, Siong Wong; Yei, Ling Chang (Institute of Electrical and Electronics Engineers Inc., 2017)
Intensive worldwide effort is speeding up the developments in the establishment of a global surveillance network for combating pandemics of emerging infectious disease. However, there is no delivery platform available to send accurate and just-in-time disease information to reach out to the community. The public can only obtain information from the newspaper, radio or social media, which sometimes may not be an accurate information and can be classified as rumors. An android-based disease monitoring system has been implemented with a strong predictive model to help create awareness in our community. This monitoring system consists of 2 parts which are (i) Online Communicable Disease Monitoring System and (ii) Android-based monitoring application. In Malaysia, public health department utilizes Communicable Disease Control Information System to collect data and monitor diseases. However, the current system only collects the data from an authorized medical personnel but not utilizes the data to help the decision makers to access and monitor the spread of disease. The proposed system aimed to enhance the current system by providing better data visualization and incorporate forecasting component by using a mathematical model. Hand, Foot and Mouth Disease (HFMD) is used as a case study to demonstrate the system. Through the mobile application, the public user can be informed with real-time epidemic disease information from the proposed system. © 2016 IEEE.